Factors Influencing Early Retirement Intention of Teacher Leaders in Secondary Schools - Norhana bt Mohamad Saad; Wan Ainul Mardhiah bt Wan Amri Faizal (International Journal of Social Learning (IJSL), 2022)
The Ministry of Education Malaysia (MOE) is committed to ensuring that teachers serve until the end of their service. However, there is an increase in the intention for early retirement among teachers. Hence, this study aimed to identify the factors influencing early retirement intention among the teacher leaders of secondary schools. Seven teacher leaders were purposely selected: senior assistants, senior teachers, heads of departments, and heads of six core subjects for Malaysian Certificate Examination from secondary schools in Kelantan, Malaysia. The qualitative data obtained through interviews were analyzed thematically. The findings analysis found eight contributing factors: lack of information technology skills, health problems, role conflict, financially stable, career satisfaction, wanting family time, filling time meaningfully, and venturing into other fields. To reduce the desire for early retirement, this study suggested that relevant partiesrelevant partiesrelevant partiesrelevant partiesrelevant parties should give all factors as contributors attention should give all factors as contributors attention should give all factors as contributors attention should give all factors as contributors attention should give all factors as contributors attention.